2013
DOI: 10.1017/jns.2013.36
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet alters expression of pathways of growth, blood supply and arachidonic acid in rat placenta

Abstract: The high fat content in Western diets probably affects placental function during pregnancy with potential consequences for the offspring in the short and long term. The aim of the present study was to compare genome-wide placental gene expression between rat dams fed a high-fat diet (HFD) and those fed a control diet for 3 weeks before conception and during gestation. Gene expression was measured by microarray and pathway analysis was performed. Gene expression differences were replicated by real-time PCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Four time points were chosen as they cover the time period from mid gestation to the day prior to labour onset (E14.25, E15.25, E17.25 and E20). These investigations are apart of a larger gene expression study [ 28 , 29 ]. The rat model allows the study of RAS compenents at time-points (mid to late gestation) difficult to be obtained from human and unlike in the mouse, placentation in the rat involves the deep invasion of trophoblast ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Four time points were chosen as they cover the time period from mid gestation to the day prior to labour onset (E14.25, E15.25, E17.25 and E20). These investigations are apart of a larger gene expression study [ 28 , 29 ]. The rat model allows the study of RAS compenents at time-points (mid to late gestation) difficult to be obtained from human and unlike in the mouse, placentation in the rat involves the deep invasion of trophoblast ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal high-fat diet upregulates the expression of placental mRNA in the arachidonic acid metabolism pathway. ( 20 ) The increase in maternal arachidonic acid that accompanies a high-fat diet would be expected to increase the fetal arachidonic acid level, which would thus upregulate the fetal expression of VEGF. Overexpression of VEGF in the myocardium inhibits the process of epithelial-mesenchymal transformation responsible for endocardial cushion formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have demonstrated that a diet high in saturated fats, often found in processed foods containing MG, may indeed increase the risk of developing CHD. High-fat diets in expectant mothers have been shown to enhance the expression of placental mRNA associated with the arachidonic acid (AA) metabolism pathway 43 . This can lead to elevated fetal arachidonic acid levels due to maternal arachidonic acid transfer, resulting in an upregulation of fetal VEGF expression 44 .…”
Section: Monoradylglycerols (Mg) Are a Type Of Lipid Molecule Charact...mentioning
confidence: 99%